The expansion of the Brazilian Federal Universities Network as a vehicle for urban and regional sustainable development - Wendel H. BAUMGARTNER (European Journal of Geography)
The present research paper aims to analyze the spatial results of the expansion that Brazilian Federal Universities Network have presented between 2003 and 2018, looking forward the impacts and possibilities towards the achievement of urban and regional sustainable development. In economically obsolete or marginalized areas or in those with strong industrial dynamism or agribusiness production, these new campuses also can be understood as vehicles to promote economic security/growth, social equity and assure environmental integrity. Focusing in two empirical studies, based in qualitative and quantitative methodologies, besides the theoretical approach, in cities and regions of Bahia state which received two new universities, we present the economic contribution of the new campuses, the challenges and strategies to socially develop places with high amount of vulnerable population, and the environmental potentialities to build green campus, understood as a nature-based solution, and to implement the Sustainable Developing Goals